FORESTRY-TAXATION STRUCTURE OF FORESTS AT THE STATE ENTERPRISE "KREMENETS FORESTRY" - Бондар, О. Б.; Ткач, Л. І.; Солодовник, В. А. (Podilian Bulletin: Agriculture, Engineering, Economics, 2019)
The study of the forestry-taxation structure of plantations plays an important role during the conduct of economic activities in the territory of forest enterprises of Ukraine. So, timely taken forestry measures will allow to increase the productivity of forest plantations in the territory of forestry enterprises in the future. The database of the Ukrderzhlisproekt JSC as of 01.01.2012 was used for the analysis of the forestry-taxation structure of forests at the State Enterprise "Kremenets Forestry". The typological diversity of forests was characterized according to the developed classification of Alekseiev-Pogrebniak. The total area of the forestry land of the state enterprise “Kremenets Forestry” for the period from 01.01.2009 to 01.01.2012 has not changed and makes up 28,9 hectares, only the area of forest crops increased by 369 hectares and areas covered with forest vegetation increased by 184 ha, the total reserve increased by 246cubic meters and a natural renewal increased by 27 hectares. The structure of areas covered with forest operational forests are prevailing, the share of which is 51 %, forests of nature protection, scientific, historical and cultural purposes – 28 %, recreational-and-health-improving forests – 19 %, and protective ones – 2 % only. The typological diversity of forests in the territory of the experimental site is characterized by a significant number of forest types. The largest area is under the fresh hornbeam forest – 12374 hectares (of which 7378 hectares (60 %) under common oak and other species), and the least area is under the raw black-alder sudubrava – 333 hectares, while other types of forests occupy 408 hectares. The largest total reserve is the pine forest, which is 2785 thousand m3, the second by the number - common oak – 2319 thousand m3, the smallest reserve is forest beech (0,5 thousand m3) and other wood species (0,3 thousand m3). The average change in the reserve at the state enterprise "Kremenets Forestry"; pine forest and common oak have the largest change (49 and 37 thousand m3), and the smallest change in the reserve is in forest beech and other wood species and makes up only 0,26 thousand m3. The average age of wood species: common oak – 67 years (the largest one), common hornbeam – 66 years, pine and silver birch – 57 years, norway spruce has the smallest average age – 33 years. By improvement cutting, the formation of plantations of good natural composition and improvement of the sanitary condition of forests is carried out in an area of about 1,4 hectares in average over the last revision period